Encounter physical geography : interactive explorations of earth using Google Earth - Porter, Jess C. (Prentice Hall ; Pearson Education [distributor], 2014)
Workbook containing interactive exercises intended for use with online explorations of Google Earth for each chapter. Each chapter directs students to a corresponding Google Earth KMZ file, available for downloading at www.mygeoscienceplace.com.